Pengaruh Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Pertanian Yang Terdaftar di Bursa Efek Indonesia - De Pinto Simanjutak, Owen; Enjang Syahputra, Heri; Idahwati; Khairiah Sembiring, Jihan (JURNAL MUTIARA AKUNTANSI, 2022)
This study aims to determine the extent of the influence of Deferred Tax Expense and Tax Planning on Earnings Management in Agricultural Companies registered on the Indonesia Stock Exchange (IDX) with an observation period of 2017-2020. This research is a quantitative research using secondary data. The data used in this study is data based on financial statements obtain through the official website of the Indonesia Stock Exchange (IDX), namely: www.idx.co.id. There are 29 populations of agricultural companies and 8 agricultural companies are take as samples with the sampling method using purpose sampling and data collection using the documentation method. The analytical method used in this study is the classical assumption test and multiple linear regression. The results showed that the deferred tax expense variable had no effect on earnings management and the tax planning variable had no effect on earnings management when tested partially. Simultaneously deferred tax expense and tax planning have a significant effect on earnings management in agricultural companies listed on the Indonesia Stock Exchange (IDX) in 2017 -2020.